2012
DOI: 10.1017/s1049023x12000659
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Transfusion: Experience in a Rural Aeromedical Transport Service

Abstract: In this rural AMTS, transfusion was an infrequent, likely life-saving, and potentially high-risk emergent therapy. Strict compliance with an established transfusion protocol resulted in appropriate and effective decisions, and transfusion proved to be a safe in-flight procedure for both patients and providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…The use of PH RBCs ranged from 1.4% to 4.0%, with trauma patients comprising 48% to 71% of patients and scene transports 9% to 53%. 2931 The proportion of scene transports in these series is consistent with the current analysis demonstrating 52% receiving PTC RBC transfusion were transported from the scene. In our matched cohort, however, three fourths of patients in each group were scene transports.…”
Section: Discussionsupporting
confidence: 82%
“…The use of PH RBCs ranged from 1.4% to 4.0%, with trauma patients comprising 48% to 71% of patients and scene transports 9% to 53%. 2931 The proportion of scene transports in these series is consistent with the current analysis demonstrating 52% receiving PTC RBC transfusion were transported from the scene. In our matched cohort, however, three fourths of patients in each group were scene transports.…”
Section: Discussionsupporting
confidence: 82%
“…Early studies demonstrated utilization of PTC RBC in a HEMS program required careful monitoring and defined arrangements with a blood bank, but overall was feasible and safe. (15, 16) As this practice became more common in HEMS programs, small studies emerged evaluating outcomes in trauma patients receiving PTC RBC transfusion. Sumida compared 17 patients receiving PTC RBC with 31 patients receiving more than 2L of crystalloid only.…”
Section: Discussionmentioning
confidence: 99%
“…(14) The capability to provide RBC transfusion during transport is generally limited to well-developed helicopter emergency medical service (HEMS) systems. (15, 16) Because of this, there is little evidence examining the use of prehospital RBC transfusion to mitigate early hemorrhage and shock in injured civilians. (17)…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, shorter time to transfusion has been associated with better survival . Positive experiences from the military setting have seen RCC administration adopted by civilian emergency medical systems …”
Section: Introductionmentioning
confidence: 99%